2011
DOI: 10.1002/alr.20072
|View full text |Cite
|
Sign up to set email alerts
|

Early postoperative care following endoscopic sinus surgery: an evidence‐based review with recommendations

Abstract: Based on the available evidence, use of nasal saline irrigation, sinus cavity debridement, and standard topical nasal steroid spray are recommended early postoperative care interventions. Postoperative antibiotic, systemic steroid, nonstandard topical nasal steroid solution, and/or drug-eluting spacers/stents are options in postoperative management. These evidence-based recommendations should not necessarily be applied to all postoperative patients and clinical judgment, in addition to evidence, is critical to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
141
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 152 publications
(153 citation statements)
references
References 40 publications
1
141
0
7
Order By: Relevance
“…Although current practices in peri-and post-operative FESS care can vary widely among otolaryngologists and are not uniformly driven by evidence-based outcome research (7), use of nasal saline irrigation, sinus cavity debridement, topical nasal steroids, antibiotics and mucolytic agents are recommended as early postoperative care interventions (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…Although current practices in peri-and post-operative FESS care can vary widely among otolaryngologists and are not uniformly driven by evidence-based outcome research (7), use of nasal saline irrigation, sinus cavity debridement, topical nasal steroids, antibiotics and mucolytic agents are recommended as early postoperative care interventions (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…702,1020 No RCTs have been done to adequately address this issue but those studies that have considered this aspect have not shown any overt problem. Bhalla et al 722 retrospectively considered 18 patients receiving budesonide irrigation and showed no reduction in morning cortisol, and in selected patients an adrenocorticotropic hormone (ACTH) stimulation test did not show hypothalamic-pituitary-adrenal (HPA) axis suppression.…”
Section: Viiie1 Crswnp Management:-saline (Spray and Irrigation)mentioning
confidence: 99%
“…In 2011, Rudmik et al 1020 published an EBRR on postoperative care after ESS and divided the types of postoperative care into several distinct categories, which are followed in this update. Additional evidence was identified for many of these categories and also on the use of Mitomycin C, so that category was added.…”
Section: Xe Surgery For Crswnp and Crssnp: Postoperative Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…[47][48][49][50] Based on the available evidence, debridement has been recommended in the early postoperative care of adult ESS patients. 51 However, no corresponding studies have been published investigating the impact of postoperative debridement on PCRS patients. In fact, several studies have shown that postoperative debridement was not necessary in children.…”
Section: Endoscopic Sinus Surgery and Turbinoplastymentioning
confidence: 99%